2012
DOI: 10.5539/ijbm.v7n3p142
|View full text |Cite
|
Sign up to set email alerts
|

Purposes of Performance Appraisal System: A Perceptual Study of Civil Servants in District Dera Ismail Khan Pakistan

Abstract: Performance Appraisal System (PAS) in the civil service of Pakistan has been established to fulfill various purposes. Previously, this aspect of PAS in the civil service has not been investigated. In this study we examine perceptions of the civil servants regarding various purposes of the PAS. Data was collected from the civil servants working in the two departments of far flung district Dera Ismail Khan, Khyber Pakhtunkhwa. The results show that appraisees have mixed responses regarding purposes of PAS. It im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 40 publications
3
46
0
Order By: Relevance
“…Several studies support the notion that perception of fairness of performance appraisal is closely related to employee's commitment to their organization (Ikramullah et al, 2011;Getnet et al, 2014;Bekele, Shigutu, & Tensay, 2014). If the employee perceive that the decision are fair, they would reciprocate with high commitment and would be willing to contribute more effort towards the attainment of organizational goals.…”
Section: Performance Appraisalmentioning
confidence: 95%
See 2 more Smart Citations
“…Several studies support the notion that perception of fairness of performance appraisal is closely related to employee's commitment to their organization (Ikramullah et al, 2011;Getnet et al, 2014;Bekele, Shigutu, & Tensay, 2014). If the employee perceive that the decision are fair, they would reciprocate with high commitment and would be willing to contribute more effort towards the attainment of organizational goals.…”
Section: Performance Appraisalmentioning
confidence: 95%
“…Furthermore it is also revealed that this performance evaluation practice can used to detect employee's perception, preferences, beliefs and developmental areas with regard to the organiztaional goals.As a results, they are valued and seen as part of organization team. Thus the employees may develop a greater commitment to their organization (Roberts, 2003;Ikramullah et al, 2011).…”
Section: Performance Appraisalmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be deduced from the results that the PAS is highly perceived by the AEP as the most effective annual evaluation performance system and the Agricultural Development program is really using PAS as one of the determining factors for employees' development. Contrary to this finding, Ikramullah, Khan, & Zaman (2012) found out in Pakistan that there is a high degree of perception from the employees that the performance appraisal system of the organisation is not used to record their performance accurately. Hence, Youngcourt, Leiva, & Jones (2007) emphasised that for PAS to be effective, AEP's perception about their performance appraisal system should form part of a larger examination of the effectiveness of the appraisal system of the organisation.…”
Section: The Perception Of Aep About the Purpose/reasons For Annual Smentioning
confidence: 51%
“…There is substantial research that examines the impact of organisational justice perceptions on employee attitudes and the role and effectiveness of managers (Geeta, Pooja & Renu, 2011;Colquitt & Rodell, 2011;Wang, Liao, Xia & Chang, 2010). With performance management being viewed as Abstract one of the most important human resources systems (Blume, Baldin & Rubin, 2009;Ikramullah, Shah, Hassan, Zaman & Khan, 2011;Tuytens & Devos, 2012), any negative attitude towards the system arising from employee perceptions is seen as causing conflict and unhappiness (Thurston & McNall, 2010). This results in lower employee productivity and may ultimately determine the success or failure of the organisation (Ikramullah, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%